Does State Street lead to Europe? The case of financial exchange innovations - Mari Komulainen; Tuomas Takalo (Bank of Finland, 2009)
We study whether and to what extent financial exchange innovations are in practice patentable in Europe. We find that exchange-related applications initially increased significantly after the State Street decision but subsequently decreased. The clear majority (65%) of applications come from the U.S. investment banks and exchanges themselves being among the most active innovators. But patents were not easly granted in response to these applications (only 3% of them led to valid patent). The high post-grant opposition rate (41%) for granted patents indicated that competitors tightly monitored each other s patents. The evidence, as augmented with clinical case studies, supports the notion that, for an invention to pass the inventive step requirement for obtaining a European patent, it should have technical features for solving a sufficiently challenging technical problem. Our evidence suggests that patentability standards for financial methods have not weakened in Europe in the aftermath of the State Street decision and that the inventive step requirement constitutes a major obstacle for applicants to overcome in order to obtain a financial exchange patent in Europe.
URN:NBN:fi:bof-20140807237
Keywords: 330